Penyuluhan Penguatan Moderasi Beragama Berbasis Kearifan Lokal Pada Masyarakat Hindu - I Wayan Ardhi Wirawan; Made Sumari; I Nengah Putra Karyana; Ida Ayu Nyoman Sutriani Sutriani; Diana Rindayanti (IAHN Gde Pudja Mataram, 2022)
Accommodating to local culture is one of the indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia. Local culture that is implemented by a number of Indonesian people is in the form of local wisdom, such as one that is implemented by the people of Banjar Sesia, Sangaran Hamlet, Selelos Village, North Lombok Regency. The extension method is carried out using two techniques, namely lectures and practice. The lecture was conducted by delivering material accompanied by an in-depth discussion of the topic of strengthening religious moderation through the implementation of local wisdom. Practices are carried out to strengthen skills related to making ceremonies which are used as a means of ceremonial implementation of local wisdom. Practice is also carried out in training the art of religious dance as a complement to the implementation of local wisdom, especially in Hindu religious rituals. Counseling in community service activities, both lectures and practices, focuses on local wisdom whose implementation involves internal Hindu community participants as well as involving the participation of interfaith communities. First, involving the internal Hindu community in the form of the implementation of Hinduism in daily life. Second, involving interfaith communities in the form of traditional traditions whose participants are from the Sasak-Islamic, Balinese-Hindu, and Sasak-Buddhist communities. Counseling is weighted on the aspect of implementing local wisdom in gluing interfaith social relations as a basis for strengthening religious moderation in order to realize social harmony. The results of community service activities are (1) knowledge about the nature of local wisdom in strengthening religious moderation; (2) skills in making ceremonial facilities and training in mastery of the art of dance used in the implementation of local wisdom. The counseling carried out is expected to contribute to strengthening religious moderation through the implementation of local wisdom.